Recent developments in data science and intelligent analysis of information : proceedings of the XVIII International Conference on Data Science and Intelligent Analysis of Information, June 4--7, 2018, Kyiv, Ukraine /: proceedings of the XVIII International Conference on Data Science and Intelligent Analysis of Information, June 4--7, 2018, Kyiv, Ukraine. (2018) - Unknown
No abstract available